2006
DOI: 10.1128/jb.188.3.1120-1133.2006
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Genes of the Cell Wall Stimulon in Clinical Isolates ofStaphylococcus aureusExhibiting Vancomycin-Intermediate-S. aureus-Type Resistance to Vancomycin

Abstract: Custom-designed gene chips (Affymetrix) were used to determine genetic relatedness and gene expression profiles in Staphylococcus aureus isolates with increasing MICs of vancomycin that were recovered over a period of several weeks from the blood and heart valve of a patient undergoing extensive vancomycin therapy. The isolates were found to be isogenic as determined by the GeneChip based genotyping approach and thus represented a unique opportunity to study changes in gene expression that may contribute to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
241
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(256 citation statements)
references
References 29 publications
14
241
1
Order By: Relevance
“…This is in agreement with the current knowledge that PBPs, besides their direct role in peptidoglycan synthesis, may interact with other proteins that could be involved in regulation of peptidoglycan biosynthesis or its degradation (68). Interestingly, fmtA expression has been reported to increase in the presence of different cell wall-active antibiotics (24,(32)(33)(34)(35). These observations support our proposal that FmtA may directly compensate for peptidoglycan biosynthesis and indirectly prevent cell wall degradation.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is in agreement with the current knowledge that PBPs, besides their direct role in peptidoglycan synthesis, may interact with other proteins that could be involved in regulation of peptidoglycan biosynthesis or its degradation (68). Interestingly, fmtA expression has been reported to increase in the presence of different cell wall-active antibiotics (24,(32)(33)(34)(35). These observations support our proposal that FmtA may directly compensate for peptidoglycan biosynthesis and indirectly prevent cell wall degradation.…”
Section: Discussionsupporting
confidence: 81%
“…This proposal is in agreement with observations that inactivation of fmtA reduces methicillin resistance and peptidoglycan cross-linking (24). It is also consistent with the recent transcriptomics studies that have identified fmtA as an active participant of the S. aureus response to cell wall-active antibiotics (24,(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Gene expression profiling is becoming an important tool to study pathogenesis of infectious diseases as it allows molecular characterization of the cellular responses of host and pathogen (Chaussabel et al 2003 ;Hromatka et al 2005 ;McAleese et al 2006). This type of study has become feasible since the introduction of 2 high-throughput expression profiling techniques : (i) microarrays, used for comparative analysis of thousands of genes in distinct RNA populations (Schena et al 1995), and (ii) quantitative real-time PCR (Q-PCR), used for rapid simultaneous analysis of a specific set of genes in large sample collections (Heid et al 1996 ;Vandesompele et al 2002).…”
Section: Introductionmentioning
confidence: 99%